What About Me? An Essay on Creating Nonprofit Ventures - Shepherd, Dean A.; Patzelt, Holger (Entrepreneurship Theory and Practice, 2025)
Although we know a great deal about creating ventures that can generate financial wealth for entrepreneurs, we have largely excluded, ignored, or “danced around” the creation of nonprofit ventures (with some important exceptions). We propose research to explore how initiating, engaging, and performing nonprofit venturing may differ from for-profit venturing and how some nonprofit entrepreneurs and their ventures differ from other nonprofit entrepreneurs and their ventures. We hope this essay convinces some entrepreneurship scholars that investigating the creation of nonprofit ventures is valuable and can add richness and vibrancy to the entrepreneurship field.